Science, technology and national socialism (Cambridge University Press, 1994)
This book provides a survey of the development of scientific disciplines and technical projects under National Socialism in Germany. Each contribution addresses a different, new aspect which is important for judging the interaction between science, technology and National Socialism. In particular, the personal conduct of individual scientists and engineers as well as the functionality of certain theories and projects are examined. All essays share a common theme: continuity and discontinuity. All authors cover a period from the Weimar Republic to the post-war period. This unanimity of approach provides answers to major questions about the nature of Hitler's regime and about possible lines of continuity in science and technology which may transcend political upheaval. The book is also the most comprehensive to date on this subject, and includes essays on engineering, geography, biology, psychology, physics, mathematics, and science policy.